Peran Lembaga Sosial Kemasyarakatan dalam Pengelolaan dan Pemanfaatan Hutan - Dwi Setiawan Chaniago; Anisa Puspa Rani; Solikatun Solikatun (Prodi Sosiologi Universitas Mataram, 2019)
Social institutions are always an entity and are considered important in society. Social institutions have some important roles including maintaining and maintaining social value and also able to complement the needs of the community. With the existence of social institutions, it is expected to maintain a value that is considered important and able to be a tool and a container championing certain interests in society. The purpose of this research is to identify the role of social institutions in the village of Karang Bajo in the management and utilization of forests and to identify the pattern of relations between the social institutions of the village community is multilateral in support of forest management and utilization. This study uses qualitative approaches and sociological perspectives. Based on the results of the research known that the role of social society in the management and utilization of forest in the village of Karang Bajo divided into three forms of institutions, namely the first traditional pranata that play a role in preserving indigenous forests with various The rules that are sourced from the values of local wisdom, second, the institution of cultural and cultural tourism that plays a role in promoting the wisdom of local cultures, natural wealth and other village potentials in developing ecotourism areas, and third The honey bee cultivation institution, which contributes to the economical utilization of forest by also preserving the forest as a source of bee feed. The pattern of relationship between community social institutions in forest management and utilization is done by multiinstitutional synergy that is complementary and mutually supportive of each other. Relations between institutions are tied to solidarity values, economic systems, tradition systems, social control, and leadership.